Anmerkungen zu 'Irrungen und Wirrungen mit der Leistungsbilanzstatistik' von Georg Erber - Jan Priewe (Wirtschaftsdienst, 2013)
In der Juliausgabe veröffentlichte der Wirtschaftsdienst einen Aufsatz von Georg Erber mit dem Titel 'Irrungen und Wirrungen mit der Leistungsbilanzstatistik'. Dazu äußert sich Jan Priewe kritisch. Anschließend stellt Georg Erber in einer Erwiderung seine Sicht dar. – – Priewe rejects several propositions: The current account balance is not a sound indicator of the competitiveness of an economy, the direct use of gross capital inflows is not pre-determined by anyone other than foreign investors, capital flows do not determine the current account balance, bilateral capital flows between member countries of the eurozone are not relevant for the balance of payment, and absolving the surplus countries and solely blaming the deficit countries for improper use of capital inflows obfuscates the fact that both surplus and deficit countries are involved in the making of imbalances. In his reply, Erber stresses that the intention of his article was to point out that the empirical facts blaming Germany for being responsible for the current eurozone crisis are not supported by the data. Furthermore, current accounts are mere accounting identities. Therefore, focussing on the current accounts alone is insufficient for identifying the causes of the euro crisis.
Keywords: F15; F21; F32; F36; F43; 330; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Eurozone; EU-Staaten